Adoption of Information and Communication Technology: a Strategy For Promoting Lecturers’ Effectiveness in Nigerian Universities - Suleiman Yusuf; Alao Monsurat Iyabo (Jurnal Educatio FKIP UNMA, 2022)
Information Communication and Technology has become a global requirement to replace the traditional teaching methods with a technology-based teaching tools and facilities at all levels of education. It is on this premise that this study examined adoption of ICT as a strategy for promoting lecturers' effectiveness in Nigerian universities.  To this end, the concept of information and communication technology with relevant theories and models were examined. Concept of lecturers’ effectiveness, usefulness of ICT and their challenges were critically examined. The challenges include inadequate power supply and poor funding.  The study concludes that the importance of ICT in Nigerian universities cannot be underestimated, hence the need for integration of ICT for effectiveness of lecturers.  The study suggests that adequate ICT facilities should be provided for lecturers to be efficient and effective in terms of teaching, research and community development.